A comparative analysis of semantics and syntax in Philippine online news outlets - Reina Mae E. Esteban; Joseree Ann L. Ferrer; Natasha Kaye R. Soriano; Rodolfo P. Dizon Jr (Journal of Education, Social & Communication Studies, 2026)
This study examines the impact and influence of semantics and syntax on Philippine online news headlines. From 2010 to 2025, findings show that news outlets increasingly adopted diverse headline styles to appeal to specific audiences, reflecting shifts in cultural, social, and political contexts. ABS-CBN emphasized cultural identity and national unity, while The Philippine Star frequently used irony to highlight societal issues. The Philippine Daily Inquirer catered to a more informed readership through complex language, whereas the Manila Bulletin prioritized clarity and simplicity for broader accessibility. Across platforms, dominant syntactic features included brevity, concise sentence structures, and the use of active voice to ensure immediacy and impact. Semantically, headlines commonly employed rhetorical devices, emotional appeal, and culturally relevant terms to enhance reader engagement. Overall, Philippine online headlines evolved significantly during the 15-year period, adapting linguistic choices to audience preferences and societal changes while retaining their core function of providing clear, compelling information.